GENE-30. PRELIMINARY STUDY ON WHOLE-EXOME SEQUENCING TECHNOLOGY IN THE GENETIC ANALYSIS OF PEDIATRIC PATIENTS WITH GLIOMAS - Lai, Mingyao (Neuro Oncol, 2019)
OBJECTIVE: To analyze the genes related to the signaling pathways in pediatric gliomas and drug-related genes with whole-exome sequencing technology. METHODS: The tumor tissues and matched blood samples of 17 enrolled patients were detected with whole-exome sequencing technology. There were 3 cases of diffuse midline gliomas, 2 cases of childhood glioblastomas, 3 cases of disffuse astrocytoma, 1 case of pleomorphic xanthoastrocytoma, 1 case of ganglioglioma, 6 cases of anaplastic ependymoma and 1 case of ependymoma in this study. All the enrolled patients who were no more than 14 years old received surgery in the Department of Neurosurgery, Guangdong Sanjiu Brain Hospital. The diagnosis was confirmed by pathological examination and the sample acquisition was approved by hospital ethics committee. RESULTS: With the use of whole-exome sequencing technology, a total of 31 related genetic mutations were detected in 15 cases, while no genetic mutation was detected in the other 2 cases. The genes related to the signaling pathways in pediatric gliomas included ATRX, ASL1, BCOR, EP300, FGFR1, H3F3A, IGF1R, MED12, PIK3R1, PRKDC, RB1, SETD2, SMARCA4, SOX2, TGFBR2, and the drug-related genes included AKT1, BCL2, BRAF, BRCA2, CCND1, CCND2, CDK6, EGFR, FGF3, KRAS, MET, PDGFRA, PIK3CA, PTEN, TP53, TSC1. One patient only had genes related to the signaling pathways, and 14 patients had drug-related genes. CONCLUSION: Applying whole-exome sequencing technology in the genetic analysis of pediatric patients with gliomas has remarkable guiding significance for revealing the mechanism of disease, searching for therapeutic targets and adopting individualized treatment, which can bring potential benefits to pediatric patients. However, more samples and further data analysis and verification are needed in future study.